Profitability of Mechanical Transplanting of Rice Farming in Nepal - Thapa, Dhan Bahadur; Amgal, Sujan (Nepalese Journal of Agricultural Sciences, 2025)
Most farmers in Nepal practice manual transplanting, which is labor-intensive and costly as well. Rice farming has considerable challenges due to labor scarcity and growing labor costs. Manual transplantation also creates delays owing to labor constraints, as well as the difficulty of handling younger seedlings during transplanting, causing older seedlings to be used, resulting in a lower yield. In such circumstances, mechanical transplanting may be the best alternative to manual transplanting since it ensures timely transplanting, involves fewer labors, maintains appropriate plant population, lowers production costs, contributes to higher yield, and is a more cost-effective technique of rice production. Despite its numerous benefits, the adoption of mechanical rice transplanting technique among Nepalese farmers is sluggish due to the majority of small-holder farmers, expensive starting costs, and a lack of knowledge about the technology related mat-type nursery growth. So, to enhance farmers' acceptance of mechanical transplanting, providing technical knowledge of raising mat type or tray nursery, as well as capacity building for custom hiring, could be a solution. This review examines the impact of mechanical transplanter on the growth, yield, and economics of rice production.